Gender-specific occupational segregation, glass ceiling effects, and earnings in managerial positions: Results of a fixed effects model - Anne Busch; Elke Holst (Institute for the Study of Labor (IZA), 2011)
The study analyses the gender pay gap in private-sector management positions based on the German Socio-Economic Panel Study (SOEP) for the years 2001-2008. It focuses on occupational gender segregation, and on the effects of this inequality on earnings levels and gender wage differentials in management positions. Our paper is, to our knowledge, the first in Germany to use time-constant unobserved heterogeneity and gender-specific promotion probabilities to estimate wages and wage differentials for persons in managerial positions. The results of the fixed-effects model show that working in a more female job, as opposed to a more male job, affects only women's wages negatively. This result remains stable after controlling for human capital endowments and other effects. Mechanisms of the devaluation of jobs not primarily held by men also negatively affect pay in management positions (evaluative discrimination) and are even more severe for women (allocative discrimination). However, the effect is non-linear; the wage penalties for women occur only in integrated (more equally male/female) jobs as opposed to typically male jobs, and not in typically female jobs. The devaluation of occupations that are not primarily held by men becomes even more evident when promotion probabilities are taken into account. An Oaxaca/Blinder decomposition of the wage differential between men and women in management positions shows that the full model explains 65 percent of the gender pay gap. In other words: Thirty-five percent remain unexplained; this portion reflects, for example, time-varying social and cultural conditions, such as discriminatory policies and practices in the labor market.
urn:nbn:de:101:1-201104113215
Keywords: J31; J16; J24; 330; gender pay gap; managerial positions; gender segregation; glass-ceiling effects; Oaxaca/Blinder decomposition; fixed effects; selection bias; Lohndifferenzierung; Weibliche Führungskräfte; Arbeitsmarktdiskriminierung; Geschlechterdiskriminierung; Schätzung; Deutschland